2014
DOI: 10.1016/j.ijsolstr.2014.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-induced wrinkling of polyethylene thin sheets: Experiments and modeling

Abstract: a b s t r a c tThis paper presents a study on stretch-induced wrinkling of thin polyethylene sheets when subjected to uniaxial stretch with two clamped ends. Three-dimensional digital image correlation was used to measure the wrinkling deformation. It was observed that the wrinkle amplitude increased as the nominal strain increased up to around 10%, but then decreased at larger strain levels. This behavior is consistent with results of finite element simulations for a hyperelastic thin sheet reported previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 21 publications
0
29
1
Order By: Relevance
“…Some other numerical studies [21] also point to such a phenomenon. On the other hand, experimental works lack to confirm this prediction.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Some other numerical studies [21] also point to such a phenomenon. On the other hand, experimental works lack to confirm this prediction.…”
Section: Resultsmentioning
confidence: 77%
“…That was a qualitative agreement, a quantitative comparison would be meaningful against simulations of plastic constitutive relations. Such a relation has been published recently [21], however that work completely lacks the investigation of emerging orthotropy during the loading process. This change in the orthotropy parameters is so significant that for some aspect ratios no wrinkling appears at all during the first extension of the specimen, but in the successive cycles it forms repeatedly (watch the video file provided as supplementary data).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22][23] From the numerous literature survey some related references are illustrated for example. Cerda and Mohadevan proposed a set of simple scaling laws and verified them by elongating polyethylene 26 Taylor et al adopted Koiter's nonlinear plate theory to simulate the wrinkling patterns observed in stretched thin elastic sheets. The numerical solutions to several equilibrium boundary-value problems are obtained and compared with existing experimental, numerical and analytical results.…”
Section: Introductionmentioning
confidence: 99%